Injury Epidemiology: The Neglected Chapter - Pal, Ranabir (Nepal Journal of Epidemiology, 2012)
Injuries are the significant public health problem and posing as the mounting global crisis upsetting families and communities across population levels. We need a multidisciplinary approach embedded in injury surveillance. A sensitization revolution is vital at all the health care levels to gather critical strength of dedicated personnel in the field of research in injury intervention.DOI: http://dx.doi.org/10.3126/nje.v2i4.7825 Nepal Journal of Epidemiology Vol.2(4) 2012 pp.216-218